PROBLEMATIKA PASAR BERSAMA UMAT ISLAM DAN SOLUSINYA - MEIRISON MEIRISON (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Muslims experience many economic, social problems due to Western pressures and the world financial crisis that makes the coolies in their own country. Data show that 40% of the world's poor are Muslims. Rasulullah S.A.W after migrating to Madinah established a market that was detached from the influence of Jewry. The market is in accordance with Islamic shari'ah based on Islamic aqidah, justice and able to grow the muslimin capital development and support the economy of society. Unity is the basis of the progress of Muslims, because the world economy is controlled by the cartel. The idea of a common market of Muslims is a way out of a prolonged Islamic crisis both internally and externally. Balance and distribution of profit-based commodities. Muslim possesses the supporting factors to develop the economy equally. Natural resources, human, skill adequate, can be used optimally. Political disputes, interdependencies, relations between regions and countries are slowly overcome with religious zeal and a sense of responsibility as Muslims will greatly assist the effort.